Comparison of Interleukin-18 Serum Levels in Patients with Breast Cancer and Idiopathic Granulomatous Mastitis - Marzieh Haghbin; Akbar Hashemi Tayer; Farnaz Abbasi; Mohammad Reza Haghshenas; Abdolreza Sotoodeh Jahromi (Middle East Journal of Cancer, 2025)
Background: Breast cancer (BC), as a global challenge, is one of the most prevalent malignant diseases among women. Idiopathic granulomatous mastitis (IGM) is a rare, chronic inflammatory breast disease that primarily affects women of fertility age. IGM mimics symptoms and radiographic patterns of BC. IL-18 plays a dual role in cancer, as it can promote tumor growth or reduce tumor growth. Therefore, this study aimed to compare the serum levels of IL-18 in BC and IGM patients.Method: This case-control study was conducted on 45 patients with BC, 25 with IGM (I), and 30 healthy individuals (C) with normal screening tests as the control group. The BC group consisted of 25 newly diagnosed BC patients (N), and 20 patients with metastatic BC (M). Specialized pathologists confirmed the histopathological pattern of BC and IGM. Enzyme-linked immunosorbent assay (ELISA) sandwich technique was used for the measurement of IL-18 serum levels. All statistical analyses were performed using SPSS-23, and GraphPad Prism. P <0.05 was considered statistically significant.Results: The serum level of IL-18 showed statistically significant higher values in the three patient groups than the control group (P < 0.001). In addition, the IL-18 levels in the M group were significantly higher than in the N and I groups (P < 0.01). There was no statistical significance between N and I groups (P > 0.05).Conclusion: IL-18 levels were significantly elevated in BC compared with the IGM and control groups. IL-18 has a potential role as a prognostic indicator in BC, particularly for patients with metastasis.